Project-Based Learning Models In 21st Century Health Education: Enhancing Collaboration and Problem-Solving Skills: A Systematic Review - Askrening, Askrening; Reni Yunus; Alvin Sicat; Sutrisman, Heny; Pajar Machmud; Chotimah, Chotimah; Adrianus Prihartanto; Rosmerry Simanjuntak; Dina Angela (International Journal of Education, Vocational and Social Science, 2025)
This research aims to explore project-based learning models in 21st century health education, with a focus on improving collaboration and problem-solving skills. Through a systematic literature review covering 15 research journals published between January 2020 and January 2024, it was found that project-based learning significantly improved students' global health competencies. Results showed improvements in communication and problem-solving skills, reflecting progress in students' capacity to think critically and collaborate in the context of global health issues. Although the results are positive, challenges such as inadequate teacher training and limited resources must be overcome to maximize the benefits of this learning model. This research provides important insights for educators and policy makers in implementing project-based learning in health education.